PENGARUH PENDIDIKAN, UPAH MINIMUM DAN KESEMPATAN KERJA TERHADAP PENGANGGURAN TERDIDIK DI JAWA BARAT - Guritno, Shinta Ulan; Muljaningsih, Sri (Journal of Development Economic and Social Studies, 2024)
Unemployment is a phenomenon that occurs in all countries, including Indonesia. Educated unemployed is someone who is looking for a job or has not worked who has a high school education and above. An increase in the workforce that is not proportional to the number of jobs will increase the number of unemployed. This study aims to analyze the effect of education, minimum wages and employment opportunities on educated unemployment in West Java Province in 2018-2021. The method used is a quantitative method using panel data regression tested using the Ordinary Least Squares (OLS) method, where the test uses the Eviews 10 program tool. The results show that education has a positive and insignificant effect on educated unemployment in West Java, minimum wage has a positive and significant effect on educated unemployment in West Java, and opportunity has a positive and insignificant effect on educated unemployment in West Java.